(untitled) (Biological Sciences - PJSIR, 2022)
In field trials, conducted at the Regional Research Station, Bangladesh Agricultural Research Institute (BARI), Ishurdi, Pabna during the crop seasons of 1989 and 1990, maize (Zea mays) inter-cropped with high yielding variety (HYV) upland summer (aus) rice (Oryza sativa) (cv. BR 21). The treatments included were varying levels of plant popu- lations; sole rice (broadcast) at 100 kg seed/ha; 100% rice +50% maize (line sowing); 100% rice +33% maize; 75% rice +33% maize; 50% rice +50% maize; 100% rice +paired row maize (100%) and sole maize at 53,333 plants/ha, Highest maize yield (4.37 t/ha) was obtained from sole maize and it was followed by 100% rice + paired row maize intercrop (4.26 t/ha). This intercrop combination also produced an additional rice yield of 1 t/ha which was nearly 50% of the yield obtained from sole rice crop (2.05 t/ha). The treatment gave each of the highest rice equivalent yield (4), Land equivalent ratio (1.47), net return (US 412/ha) and benefit-cost ratio (2.50).